Serum amylase and lipase levels in type 2 diabetes mellitus - Tanvi, Noor E Jannat; Akhter, Qazi Shamima; Nahar, Sharmin; Sumi, Mahmuda Nasrin; Hosen, Mobarak (Journal of Bangladesh Society of Physiologist, 2018)
Background: In diabetes mellitus, impaired pancreatic endocrine activity may affect its exocrine function causing mal digestion and malnutrition. Objective: To assess serum amylase and lipase levels in subjects with type 2 diabetes mellitus (T2DM). Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from January 2015 to December 2015. Fifty type 2 diabetic subjects with age ranging from 40 to 55 years of both sexes were enrolled in this study and 50 age matched healthy subjects were control group. Patients were enrolled from Outpatient Department of Endocrinology, Dhaka Medical College Hospital, Dhaka. Serum amylase and serum lipase levels were estimated by spectrophotometry. For statistical analysis, unpaired Student ‘t’ test was done. Results: In this study, serum amylase and lipase levels were significantly lower (P<0.001) in comparison to control group. Conclusion: From this study, it is concluded that, exocrine derangement of pancreas may occur in type 2 diabetes mellitus. Bangladesh Soc Physiol. 2017, December; 12(2): 52-56